Morphology and physiology characteristic of some varities of rice under salinity stress - Wan Arfiani Barus; Abdul Rauf; B. Sengli Damanik; . Rosmayati (Syiah Kuala University, 2013)
This experiment was aimed to evaluate yield potential and adaptability of some varieties of rice based on some morphological and physiological characters. This study was conducted at Paluh Merbau village, Percut Sei Tuan Sub-District, Deli Serdang District, North Sumatera, Indonesia on March 2012 till July 2012. This research was arranged in a randomized block design non factorial with three replications. Eight varieties used are Ciherang, IR 64, Lambur, Batanghari, Banyuasin, IR 42, Inpara 10 and Margasari. Salinity stress in rice leads to changes in both morphological and physiological characters of plants, where the response of each genotype varies depending on the nature of tolerance or sensitivity to salt stress. Observation of growth and production showed that genotif IR 42 had the best growth and the highest production as compared with other varieties